TWOMEN TRAFFICKING: AN ANALYSIS OF EPIDEMIOLOGICAL RECORDS IN CEARÁ - Gomes Filgueira, Samily (Cadernos ESP, 2024)
The present manuscript aims to stimulate a reflection on the practice of Women Trafficking as a form of violence against women and, consequently, a public health issue. The central objective is to analyze the epidemiological data present in the Information System of Injuries and Notification - SINAN, regarding Women Trafficking in Ceará. A quantitative approach was adopted as the method, involving tabulation and data analysis. The results reveal epidemiological underreporting but allow the identification of prevalence within the victims’ profile. The discussion is based on intersectional feminism, considering the confluence of vulnerabilities gathered from the records. The final considerations point to the need for the expansion and strengthening of public policies to address the issue.